Response of Broiler Chickens Fed Boiled Red Kidney Bean (Phaseolus vulgaris) Seed Meal as Protein feedstuff on Haematology and Serum Biochemical indices (British Journal of Multidisciplinary and Advanced Studies, 2023)
Eight week feeding trial was conducted to determine the effects of dietry levels of Boiled red kidney bean meal (BRKBSM) in potassium carbonate solution on haematology and serum biochemical indices of broiler chickens. A total of 200 day old chicks (Anak 2000) were randomly allotted to five treatment diets (T1-T5) in a completely randomized design. Each treatment group was replicated 4 times with ten birds per replicate. T 1 contained 0% Boiled Red Kidney Bean Seed Meal (BRKBSM) as the control diet, while T2-T5 contained 25,50 75 and 100% inclusion levels of BRKBSM respectively. Results of the haematology and serum biochemical indices at finisher phase showed that Mean Corpuscular Volume (MCV) and Mean Corpuscular Haemoglobin Concentration (MCHC) were significantly (P0.05) affected by the diets. Albumin values (3.19 g/dl) was highest on birds fed 50% BRKBSM, globulin values was also highest at 50% BRKBSM while cholesterol values decreased with increasing levels of inclusion of BRKBSM from 0% to 100%. It is therefore concluded based on this study that BRKBSM can be included in broiler chickens diet up to 50% level without any detrimental effects on blood profile of broiler chickens.